Rinjani Global Geopark Education for Mataram Muhammadiyah Middle School Students - Hidayat, Syamsul; Erintina, Melinda Dwi; Ubaidillah, Aji Syailendra (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Management and utilization of Geoparks as a unity of geological, biological and cultural diversity will be achieved optimally if all stakeholders are involved. This service activity aims to provide Rinjani-Lombok Global Geopark (RLGG) education to Muhammadiyah Mataram Middle School students as an effort to help encourage the implementation of the RLGG educational mission to school-age youth in Mataram City. The methods applied in this service activity include needs analysis and location selection, presentation of material about RLGG to students as well as questions and answers or student responses related to educational material. In educational activities, it was conveyed that the richness/diversity in the geopark area is divided into 3 large elements, namely geological diversity, biodiversity and cultural diversity. Geoparks as a means of public education are carried out to provide an understanding of the unique geology, biology and culture as well as an understanding of the importance of conservation. Education about RLGG for junior high school students is carried out to provide understanding and give birth to a love of nature and its surroundings, a love of natural sciences and a medium for cultivating Tawheed towards Allah SWT. Sites (Geodiversity) in the RLGG Environment are sites that are associated with geological phenomena.